2016
DOI: 10.1590/0103-8478cr20150454
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Clostridium difficile infection in hamsters using a non-toxigenic strain

Abstract: The present study aimed to evaluate five nontoxigenic strains of Clostridium difficile (NTCD) in vitro and to select one strain to prevent C. difficile (CDI) infection in hamsters (Mesocricetus auratus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…It is known that spore production increases with incubation time, and recent studies have shown that even nonendemic strains can sporulate at high rates [25,33,41]. In this context, NTCD Z31 seems to be a strain with a relatively high sporulation rate, confirming a prior study where NTCD Z31 was the most efficient strain in spore production when compared to four NTCD isolated from different animals [22]. This is an important feature to consider for its possible use as a commercial preventive method, because the administration of spores, and not vegetative cells, has been shown to prevent the disease in piglets [12,20].…”
Section: Growth and Sporulationsupporting
confidence: 81%
See 4 more Smart Citations
“…It is known that spore production increases with incubation time, and recent studies have shown that even nonendemic strains can sporulate at high rates [25,33,41]. In this context, NTCD Z31 seems to be a strain with a relatively high sporulation rate, confirming a prior study where NTCD Z31 was the most efficient strain in spore production when compared to four NTCD isolated from different animals [22]. This is an important feature to consider for its possible use as a commercial preventive method, because the administration of spores, and not vegetative cells, has been shown to prevent the disease in piglets [12,20].…”
Section: Growth and Sporulationsupporting
confidence: 81%
“…The complete sequence of the NTCD Z31 genome showed some desirable genes for virulence factors not related to toxin production, such as intestinal colonization (slpA) and biofilm formation (fliC and fliD), which are likely to be important from the perspective of competitive exclusion [21]. This strain also showed a higher spore production than other NTCDs previously isolated and it prevented CDI in 100% of exposed hamsters [22].…”
Section: Strainmentioning
confidence: 82%
See 3 more Smart Citations